Isolation and Identification of Pathogenic Bacteria from Domestic Retail Fish Market at Zliten City, Libya - Elsharif , Mustafa; Ali, Mostafa; Saleh , Fauzi; Abokhras, ABoashia (Libyan Journal of Science &Technology, 2022)
The microbial load of both fish and fish products has been a cause of concern to consumers, and the industry itself. The present study was focused on isolation and identification of pathogenic bacteria found in selected species of fish taken at the city market of Zliten, Libya. Thirty-five fish samples were analyzed; the bacterial counts and identification of potentially isolated-bacteria were carried out by using standard bacteriological procedures. The sensitivity test was determined by the disc-diffusion method. The results have shown the highest bacteria count was reported for the gills of Euthynnus alletteratus (7.61´106 cfu/mL) compared to Sarpa salpa and Scomber japonicas (1.82´106 cfu/mL and 4.45´106 cfu/mL) respectively. The whole fish of Euthynnus alletteratus had also the highest bacterial count (7.589´106 cfu/mL) followed by the intestine of Sarpa salpa (6.07´105 cfu/mL) and Scomber japonicas (2.22´106 cfu/mL). Bacteria identified from this study include Staphylococcus spp. and Staphylococcus aureus, Bacillus, Pseudomonas Vibrio spp. The higher levels of Staphylococcus spp. was observed for Euthynnus alletteratus and Scomber japonicas (P<0.0043) compared to Euthynnus alletteratus. No Significant differences were observed in the microbial load between the domestic and imported fish. However, the ratio of the isolated Bacillus spp. was higher (P<0.02) in imported fish (Scomber japonicas) compared to domestic fish. Isolated bacteria from fish samples were tested for resistance against thirteen antibiotics (Penicillin, Vancomycin, Clindamycin, Cefoxitin, Oxacillin, Linezolid, Cephalexin, Rifampicin, Streptomycin, Tetracycline, Erythromycin, Gentamicin and Ampicillin). Among the isolated bacteria, the Staphylococcus spp. was resisted to different antibiotics whereas one hundred present of (Cephalexin and Rifampicin). The Staphylococcus aureus was resistance to Tetracycline and Vancomycin. Bacillus spp. was resistance to Vancomycin whereas the Pseudomonas was resistance to Rifampicin. Even though, the isolated bacteria were sensitive to different antibiotic.